Design Of A Portable Mini Pump It Up System Based On Mini Computer For Children's Gross Motor Improvement - Prima, Lucky; Anandika, Arrya; Purbolingga, Yoan; Syahputra, Ronaldo (Universitas Andalas, 2024)
The increasing influence of smartphones on young children has raised concerns about the delayed development of gross motor skills, particularly in early childhood. This issue is significant in Indonesia, which ranks fifth in ASEAN for birth rates, resulting in a large population of children at risk. Excessive smartphone use by children leads to decreased physical activity, potentially causing health problems such as obesity and reduced physical fitness. The objective of this study is to design and develop a portable system, called the